Musculoskeletal disorder risk level evaluation of posterior maxillary tooth extraction procedures - Anggy Prayudha; Roberto M. Simandjuntak; Ni Putu Mira Sumarta (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: The professional activity of dentists involves a relatively small treatment area, namely; the oral cavity. Dental treatment requires a high level of precision with the result that dentists frequently perform their duties in a physically uncomfortable position over a relatively extended period of time. Tooth extraction is the most common form of treatment performed in a standing position, with extraction of the posterior maxillary tooth being the most challenging. 80 per cent of students and dentists working in the Faculty of Dentistry at the University of Indonesia present musculoskeletal disorders (MSD). Purpose: To evaluate the level of MSD risk of Oral and Maxillofacial Surgery Clinic students at the Universitas Airlangga Dental Hospital following posterior maxillary tooth extraction. Methods: The evaluation of MSD risk level was performed over a period of three months on 73 subjects who had experienced posterior maxillary tooth extraction, categorized as extraction under anaesthesia, extraction involving the use of an elevator and extraction using forceps. Evaluation was conducted by two observers by means of CCTV video footage using a Rapid Entire Body Assessment (REBA) worksheet. Results: Under anaesthetic sedation, 67.12% experienced medium risk, 31.51% high risk, and 1.37% low risk. During extraction using an elevator, 58.90% experienced high risk, 35.62% medium risk and 5.48% extremely high risk. During extraction using forceps, 57.53% ran medium risk, 39.73% high risk, and 2.74% extremely high risk. Conclusion: Students who performed posterior maxillary tooth extraction could be categorized as running a high risk of MSD during extraction using an elevator, but medium risk when administering anaesthesia and performing extraction with forceps.